Prevalence of ascaris lumbricoides, Trichuris trichiura and enterobius vermicularis in the hands of preschool children in Day Care Centers in Miagao, Iloilo - Abellon, Ruperto L. III; Arbizo, Mark David L.
The hands of 99 preschool in Day Care Centers of Miag-ao were swabbed and examined for the presence of parasitic ova, specifically soil-transmitted parasites. prevalence rates of parasitic ova were determiend and tested for significant differences with variables that include age, sex, parent's educational level, and location of the day care center of the preschoolers. Ascaris had a prevalence rate of 24.12